Use of Partial Purified Lipase From local Chicken kidney for Improvement the Flavor of Butter Fat - Al-Hasnawi, A. N.; Al-Soufi, M. A.; Aziz, R. A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Lipase was extracted by Sodium acetate buffer (pH=6; 0.05M) Containing 0.1M NaCl. Enzyme content of crude extract was concentrated by gradual addition of ammonium sulfate at 30-60% saturation. The dialyzed extract was purified on ion-exchange chromatography through DEAE–Cellulose and gel-filtration chromatography through sephacryl S-200 column. The specific activity, enzyme yield and fold purification were 54.06 unit/mg, 42.6% and 10.88 respectively. The molecular weight of the Lipase was 43.651 KDa as determined by gel-filtration chromatography through sephacryl S-200 column. Partial purified lipase used for the improvement of the flavor of butter fat after 12 hours for storage.